2010
DOI: 10.1111/j.1558-5646.2010.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Evolved Host Breadth in the Initial Emergence of an Rna Virus

Abstract: Understanding how evolution promotes pathogen emergence would aid disease management, and prediction of future host shifts. Increased pathogen infectiousness of different hosts may occur through direct selection, or fortuitously via indirect selection. However, it is unclear which type of selection tends to produce host breadth promoting pathogen emergence. We predicted that direct selection for host breadth should foster emergence by causing higher population growth on new hosts, lower amongpopulation varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 71 publications
5
66
0
Order By: Relevance
“…During alternating passage, selection may be focused on maintaining replication competence in both hosts, by favoring generalist genomes of relatively high fitness for both cell types (49). In this case, maximum genetic diversity may not be reached, as minority mutations that would drift the mutant spectrum away from overlapping regions of invertebrate and vertebrate sequence space would be removed by purifying selection with each alternating passage.…”
Section: Discussionmentioning
confidence: 99%
“…During alternating passage, selection may be focused on maintaining replication competence in both hosts, by favoring generalist genomes of relatively high fitness for both cell types (49). In this case, maximum genetic diversity may not be reached, as minority mutations that would drift the mutant spectrum away from overlapping regions of invertebrate and vertebrate sequence space would be removed by purifying selection with each alternating passage.…”
Section: Discussionmentioning
confidence: 99%
“…First they arise in populations exposed to temporally variable habitats, when purifying selection can act to purge environment-specific deleterious mutations. Second, they arise in populations evolving in one or a few environments when conditionally deleterious mutations fail to arise stochastically [10]. Unlike under directional selection, where generalists have a slower sojourn time to high fitness in the environment shared with the specialist [38] (figure 3a), under mutation accumulation there need not be a difference in the rate of fitness gains in the shared environment for parallel evolving populations of specialists and generalists because the adaptive alleles being fixed in the two types of populations are the same ( figure 3b,d).…”
Section: Non-epistatic Magnitude Pleiotropymentioning
confidence: 99%
“…In this example of epistatic pleiotropy, cost-free generalists can arise in three ways, depending on the environments to which populations are exposed, and on the order in which mutations arise [10]. First, in populations beginning at genotype ab in a temporally variable habitat, purifying selection will purge mutations to aB, maintaining ab in the population until the cost-free generalist Ab arises and can become fixed.…”
Section: Epistatic Pleiotropymentioning
confidence: 99%
“…49,50 The formal prediction was that VSV populations experiencing direct selection for host range would have higher mean growth and less variance in mean growth on a collection of challenge hosts, compared to VSV populations that were either relatively specialized or indirectly selected for host range. 51 When challenged to grow on four novel hosts in vitro, the viruses that had been selected for generalism exhibited higher or equivalent host growth, lower among-population variance in host growth, and lower variance in population growth across hosts. Thus, these three predictions relating to the hypothesis were generally supported because direct selection for host breadth more often allowed successful emergence.…”
Section: Testing Relationships Between Robustness and Pathogen Ementioning
confidence: 99%
“…The results suggested that determination of current niche breadth should be further investigated as a potentially useful indicator in predicting pathogen emergence. 51,52 Because these many recent empirical breakthroughs in the study of robustness have involved microbes, one might predict that infectious disease is the primary biomedical realm where these robustness results might have an immediate, practical impact. Below we describe three examples of biomedically important human disease systems where robustness theory appears highly relevant.…”
Section: Testing Relationships Between Robustness and Pathogen Ementioning
confidence: 99%